EFEKTIFITAS MEDIA APLIKASI EDUKATIF DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF BAGI ANAK KESULITAN BELAJAR - Africos Yanda, Damri, Elsa Efrina (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was background by the problems that researcher found in state junior school (SD) 18 Koto Luar Padang, a child with learning disability in class II SD is having problems in recognizing words. The research aims to demonstrate the effective use of educational application media to improve children in recognize words. Research was approached by Single Subject Research, with A-B-A design. Using technique of visual data analysis chart. The result is, educational application media can improve the ability to recognize words for children with  learning disability.